Electrochemical Dictionary edited by Allen J. Bard, György Inzelt, Fritz Scholz. - Bard, Allen J.; Bard, Allen J.; Inzelt, György.; Inzelt, György.; Scholz, Fritz.; Scholz, Fritz. (Springer Berlin Heidelberg : Imprint: Springer, 2008)
The Electrochemical Dictionary provides up-to-date, broad and authoritative coverage of the specific terms most used in electrochemistry and its related fields, including relevant areas of physics and engineering. This modern compendium will be an indispensable source of information for scientists, engineers, and technical staff active in all fields of electrochemistry. The more than 2.770 entries have been written by a distinguished panel of eminent electrochemists. Each entry supplies a clear and precise explanation of the term and provides references to the most useful reviews, books and original papers to enable readers to pursue a deeper understanding if so desired. The Electrochemical Dictionary will also be appreciatively consulted by scientists working in adjacent sciences and technologies, who need a quick understanding of the electrochemical terms they encounter. More than 300 figures and illustrations elaborate the textual definitions. The Electrochemical Dictionary also contains biographical entries of people who have substantially contributed to electrochemistry.